2017
DOI: 10.1007/s10802-017-0263-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective Visual Attention Towards Oneself and Associated State Body Satisfaction: an Eye-Tracking Study in Adolescents with Different Types of Eating Disorders

Abstract: The development of eating disorders is associated with a body-related attentional bias. Although eating disorders are especially prevalent in adolescence, so far, no study has analyzed gaze patterns and state body image in response to viewing one's own body in youth. To fill this gap, the present study aimed to examine a body-related attentional bias and state body satisfaction in adolescents with various forms of eating disorders. Girls with anorexia nervosa, restrictive type (AN-R; n = 30), anorexia nervosa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
63
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 82 publications
10
63
1
5
Order By: Relevance
“…In contrast, several studies in the field of eating disorders found differences regarding the exploration pattern of body stimuli in anorexia nervosa (e.g. [30,31,32,33,34]) and bulimia nervosa (e.g. [34,35,36,37]) compared to healthy controls.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, several studies in the field of eating disorders found differences regarding the exploration pattern of body stimuli in anorexia nervosa (e.g. [30,31,32,33,34]) and bulimia nervosa (e.g. [34,35,36,37]) compared to healthy controls.…”
Section: Discussionmentioning
confidence: 87%
“…In line with these theoretical assumptions, previous research has found that females with body image disturbance or diagnosed eating disorders show an attentional bias when looking at their own body (e.g., Bauer et al, 2017;Jansen, Nederkoorn, & Mulkens, 2005;Tuschen-Caffier et al, 2015). According to a substantial number of studies, this bias seems to be characterized by stronger attention to self-defined unattractive body areas of one's own body (e.g., Bauer et al, 2017;Jansen et al, 2005;Roefs et al, 2008;Tuschen-Caffier et al, 2015). However, some studies contradict these findings.…”
mentioning
confidence: 85%
“…Participants were asked to look at the body pictures, but did not receive any further instructions in order to minimize the influence on their natural gaze behavior and thus enhance ecological validity. As this study was part of a larger project on various aspects related to body-related attention (see Bauer et al, 2017), participants were also presented with an additional photo set of an unknown female's body. This additional photo set-consisting of four body pictures which were taken under the same conditions as the participants' individual photos-was shown either before or after the set of own-body pictures.…”
Section: Positive and Negative Affect Schedulementioning
confidence: 99%
“…With regard to the cognitive‐affective component, previous studies employing various questionnaires found that women with ED report a higher dissatisfaction with their own body than do women without ED (Cash & Deagle, ; Hrabosky et al, ; Vossbeck‐Elsebusch et al, ). In line with these self‐ratings, studies in which participants were asked to evaluate characteristics of their own body found that women with ED rate their own body more critically than do nonclinical controls, that is, as less attractive or with more body fat (Bauer et al, ; Horndasch et al, ; Von Wietersheim et al, ). To establish whether such a negative view of one's own body is “justified,” Jansen, Smeets, Martijn, and Nederkoorn () asked two community panels to rate the attractiveness of bodies of women with similar body mass indexes (BMI), but with higher or lower levels of ED symptoms, and compared their ratings with the self‐ratings provided by these women.…”
Section: Introductionmentioning
confidence: 92%